Analysis of Misconceptions in High School Mathematics - Lauren C. Schnepper; Leah P. McCoy (Networks: An Online Journal for Teacher Research, 2013)
Research on teachers’ ability to identify and address student “errors” asserts that because many students who are not proficient in basic math skills demonstrate numerous mathematics misconceptions, it is essential for teachers to recognize various misconceptions when adjusting instruction (Riccomini, 2005). The research of Stefanich and Rokusek (1992) affirms that when a pattern of error was diagnosed and instruction was directed to remediate the incorrect procedure, then new learning could take place quickly, and retention appeared to be long-term. Correspondingly, a study by Wilcox and Zielinski (1997) concluded that assessment helped teachers gain better insights into their students’ understanding, including misconceptions, and therefore helped to better diagnose error patterns and remediate them.